2001
DOI: 10.1006/jnth.2001.2669
|View full text |Cite
|
Sign up to set email alerts
|

Transcendence of Sturmian or Morphic Continued Fractions

Abstract: We prove, using a theorem of W. Schmidt, that if the sequence of partial quotients of the continued fraction expansion of a positive irrational real number takes only two values, and begins with arbitrary long blocks which are ''almost squares,'' then this number is either quadratic or transcendental. This result applies in particular to real numbers whose partial quotients form a Sturmian (or quasi-Sturmian) sequence, or are given by the sequence (1+ (NnaM mod 2)) n \ 0 , or are a ''repetitive'' fixed point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
1
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 45 publications
3
100
1
6
Order By: Relevance
“…Let us prove the converse. Let α be as in the statement of the theorem, that is, for each pair of positive integers (s, t) with s > 1 there are only finitely many indices k for which (3) (a k , a k+1 ) = (s, t) or (a k , a k+1 , a k+2 ) = (1, 1, t).…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…Let us prove the converse. Let α be as in the statement of the theorem, that is, for each pair of positive integers (s, t) with s > 1 there are only finitely many indices k for which (3) (a k , a k+1 ) = (s, t) or (a k , a k+1 , a k+2 ) = (1, 1, t).…”
Section: 3mentioning
confidence: 99%
“…There are a number of recent papers on powers of words occurring in Sturmian sequences (see for instance [1,2,3,6,8,9,16,17,27,32,38,41]). Quantities of interest include the supremum of powers of factors of a sequence (the index or critical exponent of the sequence), and the limit superior of powers of longer and longer factors of the sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As much of the first part is easily derivable from the n = 2 case described in some detail in [1], we will be brief in our exposition.…”
Section: Proposition 21 the Following Inequalities Holdmentioning
confidence: 99%
“…If (u m ) m 1 is an infinite sequence with u m ∈ Σ for each m 1, then we let u be the infinite word u 1 and that this bound can be attained. If we assume that |Σ| = 2 and that u takes each of the two values with a frequency (see Definition 3.1), then the authors of [1] have shown that L(u) < 1.13, irrespective of the particular elements of Σ. In § § 2 and 3, we extend this result to any finite set, on the assumption that u takes each of the values in Σ with a frequency.…”
Section: Introductionmentioning
confidence: 99%